2006
DOI: 10.1134/s106378340612016x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anomalous dispersion on the optical characteristics of a quantum well

Abstract: Frequency dependencies of optical characteristics (reflection, transmission and absorption of light) of a quantum well are investigated in a vicinity of interband resonant transitions in a case of two closely located excited energy levels. A wide quantum well in a quantizing magnetic field directed normally to the quantum-well plane, and monochromatic stimulating light are considered. Distinctions between refraction coefficients of barriers and quantum well, and a spatial dispersion of the light wave are taken… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In our recent paper [15], we analyzed the situation where the interaction of the electromagnetic wave with the electronic system cannot be considered a small perturbation, the nonequalities kd ≠ 0 and ν ≠ ν 1 are satisfied, and the quantum well contains two closely spaced excited energy levels. It was demonstrated that the above functions can be written in the form…”
Section: Fourier Transforms Of the Electric Field Of The Transmitted mentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent paper [15], we analyzed the situation where the interaction of the electromagnetic wave with the electronic system cannot be considered a small perturbation, the nonequalities kd ≠ 0 and ν ≠ ν 1 are satisfied, and the quantum well contains two closely spaced excited energy levels. It was demonstrated that the above functions can be written in the form…”
Section: Fourier Transforms Of the Electric Field Of The Transmitted mentioning
confidence: 99%
“…The function N involves the complex quantity ε = ε' + iε'', which has the following form [3,13,15]: (13) This quantity accounts for the influence of the spatial dispersion on the radiative broadening ε'γ rj and the shift ε''γ rj of the energy levels of the doublet.…”
Section: Fourier Transforms Of the Electric Field Of The Transmitted mentioning
confidence: 99%
See 3 more Smart Citations